Effects of timing of nitrogen side-dressing application in sunflower with and without weed control. - Fleck, Nilson Gilberto; Silva, Paulo Régis F. da (Pesquisa Agropecuaria Brasileira, 2014)
With the objective of determining the effects of timing of nitrogen (N) side-dressing application on grain yield and other agronomic traits of sunflower (Hlianthus annuus L.) ’cv. Contisol 711’ and to evaluate the possible interaction that it could exert on weeds as a cultural method of control, this research was carried out at Guaíba, RS, Brazil, in the growing seasons of 1985/86 and 1986/87. Treatments were composed by presence and abscence of weeds, application of 80 kg/ha of N, at V4, V10_11 , R1 and R3 growth stages, according to the scale of Schneiter and Miller (1981), and by a check without N application. Weed presence during all plant cycle decreased grain yield by 12%. The response of sunflower to the timing of N application occurred only in the 1986/87 growing season, when grain yield decreased linearly as the timing of N application was delayed from V4 to R3 stage. Only in the second growing season N application reduced grain oil content in relation to the check treatment. Timing of N application did not affect this characteristic. Manipulation of timing of N application could not be considered an efficient auxiliary method in sunflower weed control.